The show - Jackson, Charles Tenney 1874-1955 (Warner Bros. Entertainment, 2012)
"Performers in a Budapest sideshow encounter love, greed, and murder." [imdb.com]
Original: USA 1927
Bildformat 1.37:1
Keywords: Film; DVD-Video